The mob and the city: the hidden history of how the mafia captured New York - Hortis, C. Alexander (Prometheus Books, 2014)
Foreword / by Dr. James B. Jacobs -- Introduction: the godfather vs. New York history -- A city built for the mob -- Prohibition and the rise of the Sicilians -- The mafia rebellion of 1928-31 and the fall of the boss of bosses -- The racketeer cometh : how the mob infiltrated labor unions -- The mafia and the drug trade -- The mob nightlife -- The lives of wiseguys -- Mouthpieces for the mob : crooked cops, mob lawyers, and prosecutors -- The assassinations of 1957 -- Apalachin -- Conclusion: New York's mafia -- Acknowledgments -- Select bibliography -- Notes